DEVELOPMENT OF MOBILE-BASED INTERACTIVE LEARNING MEDIA FOR INTELLECTUAL DISABILITY STUDENT IN ISLAMIC RELIGIOUS LESSONS - Afdhil Hafid; Iga Setia Utami (Lembaga Layanan Pendidikan Tinggi Wilayah X, 2023)
Technology can help students learn new skills and offer specialized learning support for those who require it, such as students with intellectual disability in special school. Intellectual disabilities are similar to a young toddler who can already discriminate good from bad (mumayyiz). When a child reaches the limit of understanding and is among those who must pray. The need to fulfill sharia commitments (taklif) is still placed on those with impairments. This research focuses on the creation of software that is both straightforward and efficient. Extreme Programming (XP) system by listening, which also helps students have a thorough comprehension of its main functions and outcomes.. By using good communication in XP (Ex, developers and users are able to decide which features are necessary for the software's use as well as how to discriminate between users, particularly those with intellectual disabilities. The results of the Black-Box Testing are show that all of the features performed as expected.